The effect of problem-based e-learning content on the learning achievement in basic computer system course (DSK) of the student of informatics engineering education department - Sindu, I Gede Partha; Paramartha, A. A. Gede Yudhi (Jurnal Pendidikan Vokasi, 2018)
This study was aimed at finding out the difference in learning achievement in basic computer system course (DSK) between the students who learned from content e-problem-based learning in experiment class and those who learned  from  conventional model in control class in learning basic computer system course. This study used quasi-experimental non-equivalent Pretest Post-test Control Group Design. There were three variables involved in this study. Two of them were  independent variable and dependent variable. The independent variable was e-problem-based learning and the dependent variable was learning achievement. Another variable which functioned as covariate was students'prior learning achievement. The population consisted of all students of the first semester in Informatics Engineering Education Department. The sample was selected by using simple group random sampling technique. An essay test was used to know the students'basic computer system learning achievement (DSK). The hypothesis was tested by  one-way analysis of co-variance (ANACOVA). The results showed that the mean score in the learning achievement of the students who learned from  content e-problem-based learning was higher than that of those  who learned from using conventional model. Content e-problem-based learning plays the role in improving students' learning achievement.